Impact of Therapeutics on Unified Immunity During Allergic Asthma and Respiratory Infections - Flores-Torres, Armando S.; Samarasinghe, Amali E. (Frontiers in Allergy, 2022)
Asthma is a common chronic respiratory disease that affects millions of people worldwide. Patients with allergic asthma, the most prevalent asthma endotype, are widely considered to possess a defective immune response against some respiratory infectious agents, including viruses, bacteria and fungi. Furthermore, respiratory pathogens are associated with asthma development and exacerbations. However, growing data suggest that the immune milieu in allergic asthma may be beneficial during certain respiratory infections. Immunomodulatory asthma treatments, although beneficial, should then be carefully prescribed to avoid misuse and overuse as they can also alter the host microbiome. In this review, we summarize and discuss recent evidence of the correlations between allergic asthma and the most significant respiratory infectious agents that have a role in asthma pathogenesis. We also discuss the implications of current asthma therapeutics beyond symptom prevention.